Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3389/fvets.2023.1116661
|View full text |Cite
|
Sign up to set email alerts
|

Development of modern immunization agent against bovine papillomavirus type 1 infection based on BPV1 L1 recombinant protein

Abstract: Bovine papillomavirus type 1 L1 protein was produced in a baculovirus expression system and purified as virus-like particles (VLPs) by affinity chromatography using lectins. The morphological integrity of VLPs was confirmed by electron microscopy. Differences between the two detected variants were deciphered by mass spectrometry of peptides (MALDI-TOF). Mice were immunized with purified VLPs in doses of 10, 25, or 50 μg in combination with 1% saponin and 15% alhydrogel per dose as adjuvants. Analysis of the hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Virus-like particles represent a promising vaccine platform for a diverse array of viruses. These particles mimic the morphological and immunological features of native virions, but cannot replicate and cause disease due to the absence of a viral genome [ 114 ]. No vaccination studies in buffaloes were identified.…”
Section: Papillomatosismentioning
confidence: 99%
“…Virus-like particles represent a promising vaccine platform for a diverse array of viruses. These particles mimic the morphological and immunological features of native virions, but cannot replicate and cause disease due to the absence of a viral genome [ 114 ]. No vaccination studies in buffaloes were identified.…”
Section: Papillomatosismentioning
confidence: 99%